Framework of Retail Store Image and Its Overall Impact on Consumer Behaviour: Investigating the impact of store image on consumer buying behaviors (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Over the last two decades, consumer behavior has changed remarkably. Consumer needs and choices have been diversifying steadily. In this extremely diversified and competitive business environment, retailers need to stay updated regarding the changing needs and choices of the customers. Thus, to develop a competitive position for themselves in the marketplace the retailers are experimenting every possible way to create a mark in the minds of the customers. They are trying to create a strong impact on their behaviors. Overall, the retailing sector has been passing through a period of sweeping revolution due to the introduction of new retailing formats. In this changing retail environment, the organized retail sector has been gaining ever-increasing importance in recent times. Moreover, with the changing nature of consumer behavior, it is the high time when the retailers should focus on the three primary aspects, viz. consumer preference, demand, and lifestyle. Together, these three aspects are playing an important role in the new retailing environment. Hence, it is essential to get an idea of the customer perception regarding the store architecture store infrastructure, store satisfaction, and what enhances store loyalty. Therefore, the study will investigate the fundamental framework of store image and its influence on the consumer behavior. This theoretical study will not only contribute significantly to the literature in this field but also will be very helpful for the professionals in this field, academicians, and retail entrepreneurs. It will enhance the knowledge of all concerned regarding the impact of store image on the consumers and how that can influence their buying behaviors.